The spoilt quilt and other frontier stories : pioneering women of the West - Enss, Chris, 1961-; Rumney, Hazel (Five Star, a part of Gale, a Cengage Company, 2019)
"The Spoilt Quilt and Other Frontier Stories, edited by Hazel Rumney, features sixteen brand-new stories that will delight historical fiction fans. These stories capture the spirit of freedom and individualism in the evolving American frontier through the early 1900s and feature pioneering women of the West who face life-changing challenges in settings that are in stark contrast to civilized society. Ranging from high-action traditional Westerns to introspective historical dramas set in the American West, readers will discover previously untold stories about the strong women that shaped the iconic American West. In this anthology, you'll enjoy stories by New York Times bestselling and award-winning authors such as Sandra Dallas, Deborah Morgan, Charlotte Hinger, Larry D. Sweazy, Sharon Frame Gay, Matthew P. Mayo, Randi-Samuelson Brown, C. K. Crigger, W. Michael Farmer, Candace Simar, P. Grady Cox, Marcia Gaye, John D. Nesbitt, Patricia Stoltey, Paul Colt, Preston Lewis. The Spoilt Quilt and Other Frontier Stories is a great addition to your Western fiction library. CATALOG"--